DEVELOPMENT OF AN EXPERIMENTAL STAND WITH A SYSTEM FOR CONTROLLING AND REGULATING THE PARAMETERS OF THE DRYING PROCESS OF THERMOLABILE DISPERSED MATERIALS IN A HORIZONTAL FLUIDIZED BED APPARATUS - KIRNYI, VIACHESLAV; YUKHIMENKO, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the results of developing an experimental stand with a system for controlling and regulating the drying process parameters of thermolabile dispersed materials in a horizontal fluidized bed apparatus. The necessity of conducting a physical experiment to research the optimal parameters of this process is justified. The requirements for the stand structure are defined, the technological scheme is justified and the technical characteristics of the equipment and range of technological parameters are determined. The design of the apparatus and the configuration of the stand with technological and auxiliary equipment are considered. A moist polydisperse mixture of quartz sand was selected as the model material. The objective of developing the stand was to study the kinetics of the drying process of iron(II) sulphate heptahydrate (iron vitriol) to its monohydrate form. The article considers a list of controlled and regulated parameters for periodic and continuous drying of dispersed materials. It sets out the requirements for the control and measurement instrumentation system and determines the composition of its elements. It also develops a multi-channel monitoring scheme and considers the system’s advantages and disadvantages. The tasks of controlling the temperature and moisture content of the material and the drying agent at the inlet and outlet of the apparatus and controlling the flow rate and pressure of the drying agent at the specified positions have been solved. An analysis has been performed, and equivalents of the control and measurement instruments have been proposed. The task of developing a basic electrical system and its composition, as well as the electrical control of wet material flow parameters and drying agent temperature, has been completed. Recommendations have been made regarding the scope of additional laboratory control of the dispersed material. Prospects and directions for the further improvement and automation of the scheme have been determined. The analysis of the particle size distribution of sand (the model material) and iron sulphate was presented, and the equivalent diameters of the materials were determined. Data on the changes in the particle size distribution of the model material within a specified range of weighing agent speeds was also presented. The results of developing an experimental stand with a system for controlling and regulating the drying process parameters of thermolabile dispersed materials in a horizontal fluidized bed apparatus form the basis for further correlation and improvement of the mathematical model, as well as optimisation of the technological process parameters.